Analysing the Effect of Social and Technological Causes on Bank 4.0 Adoption in Indonesia - Riandi, Muhammad Hafiz; Hapsari, Raditha; Hussein, Ananda Sabil; Parwati, Kardina Yudha; Alam, Muhammad Dimar (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study investigates various determinants affecting the Behavioural Intention (BI) of individuals to embrace Bank 4.0 in the age of digitalization. These determinants encompass both technological aspects, specifically Technology Anxiety (TA) and Technology Trust (TT), as well as a social factor known as Social Influence (SI). This scholarly investigation focuses on a comprehensive analysis of how Technology Anxiety, Technology Trust, and Social Influence collectively influence individuals' willingness to embrace Bank 4.0. Moreover, this research delves into the nuanced role of Social Influence in shaping both Technology Anxiety and Technology Trust. To gather empirical data, this scholarly work employs structured questionnaires. Subsequently, the collected data undergoes rigorous analysis using the Partial Least Square Method implemented through SmartPLS 3.2. The study's outcomes unveil crucial insights. Firstly, a significant and positive association is evident between Social Influence (SI) and Behavioural Intention (BI). Conversely, Technology Anxiety (TA) exhibits a noteworthy inverse relationship with BI. Intriguingly, Technology Trust (TT) does not demonstrate a statistically significant impact on BI. Additionally, it is worth noting that SI does not significantly influence either TA or TT. These findings underscore the importance for practitioners in the realm of Bank 4.0 to holistically consider both social and technological factors.